2022
DOI: 10.1021/jacs.2c05303
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Record-Efficiency Organic Solar Cells upon Tuning the Conformation of Solid Additives

Abstract: Volatile solid additives (SADs) are considered as a simple yet effective approach to tune the film morphology for high-performance organic solar cells (OSCs). However, the structural effects of the SADs on the photovoltaic performance are still elusive. Herein, two volatilizable SADs were designed and synthesized. One is SAD1 with twisted conformation, while the other one is planar SAD2 with the S···O noncovalent intramolecular interactions (NIIs). The theoretical and experimental results revealed that the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 58 publications
3
103
0
Order By: Relevance
“…As summarized in Figure 3c, the intensities of the absorption spectra almost kept unchanged after exposure to light for 60 h. Figure 3d exhibits photographs of TPD-TT and TPD-BT films under different times of light exposure; it is obvious that these films remain their original color after 60 h continuous illumination. Compared with the tetrahedron sp 3 bridge carbon containing acceptors like ITIC 45 and ID4F, 18 TPD-TT and TPD-BT exhibit better photostabilities, which could be attributed to the absence of a tetrahedron sp 3 bridge carbon and the utilization of β-alkyl/alkoxy chains on the periphery of the D units. The intrinsic photostabilities could provide additional stabilities for devices based on them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in Figure 3c, the intensities of the absorption spectra almost kept unchanged after exposure to light for 60 h. Figure 3d exhibits photographs of TPD-TT and TPD-BT films under different times of light exposure; it is obvious that these films remain their original color after 60 h continuous illumination. Compared with the tetrahedron sp 3 bridge carbon containing acceptors like ITIC 45 and ID4F, 18 TPD-TT and TPD-BT exhibit better photostabilities, which could be attributed to the absence of a tetrahedron sp 3 bridge carbon and the utilization of β-alkyl/alkoxy chains on the periphery of the D units. The intrinsic photostabilities could provide additional stabilities for devices based on them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The conjugated frameworks of these acceptors are planar, which facilitates charge transfer between molecules. Meanwhile, the sp 3 hybridized bridge carbons (sp 3 -C) on the fused ring are connected with the side chains that are orthogonal to the conjugated backbones to provide steric hindrance, which could inhibit the excessive self-aggregation of acceptors, thus obtaining the ideal active layer morphologies. Combined with an electron-deficient core-based fused ring unit (DA′D) and pyrrole containing donor motif, Zou et al designed a star NFA named Y6 in 2019.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution-processed organic solar cells (OSCs) have emerged as a promising competitor for the next-generation photovoltaic technology due to their low carbon footprint, lightweightness, semitransparency and so on. [1][2][3][4][5][6][7] In particular, all-small-molecule (ASM) OSCs have attracted tremendous industrial interest due to their well-dened chemical structures, high purity, and excellent reproducibility. [8][9][10][11][12] However, defects in the active layer (AL) morphology are a big challenge in enhancing the power conversion efficiencies (PCEs) of ASM-OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the research community has dedicated great efforts to control morphology to further evaluate PCEs. 4,13,14 Sun et al, in 2021, demonstrated that a volatile additive, namely dihalogenated 1,1-dicyanomethylene-3-indanone (IC-FI), can enhance the PCE of BTR-Cl/N3 based ASM-OSCs from 13.36% to 14.43%. 15 In 2020, our group induced PC 71 BM material as a ternary component into the BTR-Cl/Y6 blend, leading to signicantly enhanced PCEs with an increase in FF from 69.63% to 77.11%.…”
Section: Introductionmentioning
confidence: 99%